Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.7150/thno.56490
|View full text |Cite
|
Sign up to set email alerts
|

ZEB1 enhances Warburg effect to facilitate tumorigenesis and metastasis of HCC by transcriptionally activating PFKM

Abstract: Metabolic reprogramming, especially Warburg effect, is a key event in tumor initiation and progression. ZEB1 plays a vital role in metastasis of various cancers. We previously found that ZEB1 was excessively expressed in hepatocellular carcinoma (HCC) and its high expression was closely correlated with metastasis and recurrence of HCC. We want to know whether glycolytic enzymes are regulated by ZEB1 and contribute to carcinogenesis and metastasis of HCC. Methods: To explore whether ZEB1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(60 citation statements)
references
References 20 publications
2
58
0
Order By: Relevance
“…They found, in two unrelated patients with PCs, the recurrent p.Ile482Met mutation of the ADCK1 gene, which encodes a putative kinase with unknown molecular function. AKAP9 and ZEB1 were found mutated in 3 cases, the first encoding a regulator of protein kinase A and presumably involved in multiple signal transduction pathways, and the second encoding a zinc finger transcription factor that acts as a transcriptional repressor and is shown to facilitate tumorigenesis and promote tumor metastasis [46,47]. Two different somatic truncating loss-of-function mutations of the FAT3 gene were identified in two sporadic PCs, suggesting this gene as a novel candidate tumor suppressor gene in parathyroid carcinogenesis, possibly regulating the Wnt signaling.…”
Section: Sporadic Parathyroid Tumorsmentioning
confidence: 99%
“…They found, in two unrelated patients with PCs, the recurrent p.Ile482Met mutation of the ADCK1 gene, which encodes a putative kinase with unknown molecular function. AKAP9 and ZEB1 were found mutated in 3 cases, the first encoding a regulator of protein kinase A and presumably involved in multiple signal transduction pathways, and the second encoding a zinc finger transcription factor that acts as a transcriptional repressor and is shown to facilitate tumorigenesis and promote tumor metastasis [46,47]. Two different somatic truncating loss-of-function mutations of the FAT3 gene were identified in two sporadic PCs, suggesting this gene as a novel candidate tumor suppressor gene in parathyroid carcinogenesis, possibly regulating the Wnt signaling.…”
Section: Sporadic Parathyroid Tumorsmentioning
confidence: 99%
“…Importantly, highly metastatic cancer cell subpopulations can exploit mitochondrial function by inducing elevated oxidative stress via increased reactive oxygen species (ROS) production [ 8 ]. Moreover, the “Warburg effect” provides evidence that glycolysis concurrently serves a supporting factor in cancer cell metastasis [ 12 , 13 ]. Finding potential targets that regulate mitochondrial activity and glycolysis could therefore provide a sound strategy for treating cancer metastasis.…”
Section: Introductionmentioning
confidence: 99%
“…ZEB1, a major transcription factor controlling the EMT, has long been recognized as an important regulator of OSCC metastasis [ 14 ]. Recent studies have demonstrated that ZEB1 also plays essential roles in regulating processes related to aerobic glycolysis [ 12 , 13 ]. However, it remains unclear whether and how ZEB1 contributes to regulating mitochondrial reprogramming and aerobic glycolysis in OSCC.…”
Section: Introductionmentioning
confidence: 99%
“…In actual fact, the carcinogenic role of PFKFB4 has been documented in a variety of malignant tumors, including in HCC ( Cai et al, 2021 ; Shen et al, 2021 ; Wang et al, 2021 ). Considering that in cancers, PFKFB4 is critically involved in enhanced aerobic glycolysis, a phenomenon termed the Warburg effect ( Chen et al, 2021 ; Zhou et al, 2021 ), and we reckoned LINC01572 might exert its oncogenic effect via PFKFB4-enhanced glycolysis. This postulation was corroborated in our study as the influence of LINC01572 on both glycolysis and HCC malignant behaviors was dependent on the PFKFB4 level.…”
Section: Discussionmentioning
confidence: 99%